Inflation, deflation, reflation : management and accounting in economic uncertainty - Wilson, J. P. (London : Business Books, 1980)
This book is a comprehensive description of accounting for price-level changes, with special attention to the British experience and solutions. There are excellent descriptions of past and present practices as well as comprehensive hypothetical examples and examples of current corporate practice. The author describes a wide range of accounting issues, such as the choice of price index and the inclusion or exclusion of monetary gains and losses. The book was not limited to external reporting issues, but also considers the implications to management of inflation and the accounting treatment of price-level changes.
Includes index.
usc 14/06/18
Loans
Keywords: Industrial management; Accounting; Inflation (Finance)